2015
DOI: 10.1039/c5dt01617g
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of heteroleptic phosphines

Abstract: Heteroleptic phosphines (R2PR(1)) are a class of essential ligands for inorganic and organometallic chemistry. However, the syntheses of these phosphines are often fraught with laborious synthetic hurdles. Consequently, a renewed interest in innovative synthetic methods to access heteroleptic phosphines is emerging. This Perspective presents an overview of modern synthetic approaches to heteroleptic phosphines as well as a discussion of the strengths and limitations of these synthetic methods. A major emphasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 75 publications
1
40
0
Order By: Relevance
“…In homogeneous transition‐metal catalysis, the optimization of the catalytic center by varying the ligand properties is a powerful tool to tune activity and selectivity . Among the various ligand types phosphines are one of the most utilized ancillary ligands, as their steric and electronic properties can be easily adjusted in a predictable manner by modification of the substituents attached to the phosphorus atom . A quantitative description of the phosphine's stereoelectronic properties is most commonly provided by the Tolman electronic parameter (TEP) and cone angle .…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…In homogeneous transition‐metal catalysis, the optimization of the catalytic center by varying the ligand properties is a powerful tool to tune activity and selectivity . Among the various ligand types phosphines are one of the most utilized ancillary ligands, as their steric and electronic properties can be easily adjusted in a predictable manner by modification of the substituents attached to the phosphorus atom . A quantitative description of the phosphine's stereoelectronic properties is most commonly provided by the Tolman electronic parameter (TEP) and cone angle .…”
Section: Figurementioning
confidence: 99%
“…[3] Aq uantitative description of the phosphine's stereoelectronicp roperties is most commonly provided by the Tolman electronic parameter (TEP) and cone angle. [4] The classical boundaries of the electron-releasing character of organophosphinesh ave been recently expanded by Alcarazo's cationic phosphines that act as very strong p-acceptor ligands, [5] while Carrow et al showed that tri(1-adamantyl)phosphine is significantly more donating than P(tBu) 3 (Figure 1). [6] Yang recently showed that proazaphosphatranes (also knowna sV erkade'ss uperbases) [7] have comparable TEP values to P(tBu) 3 (Figure 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…By and large, during the second half of the past century, studies on transition metal complexes focused on alkyl and aryl phosphines such as PMe 3 , P i Pr 3 , P( c ‐C 6 H 11 ) 3 , PPh 3 and others. Notwithstanding the versatility of these ligands, relatively little progress was made on the synthesis of monodentate phosphines until fairly recently . Some twenty years ago, Buchwald and co‐workers demonstrated that when bound to palladium, dialkylbiaryl phosphines were able to catalyse with high proficiency C−C and C−N coupling reactions of aryl halides, including unactivated aryl chlorides .…”
Section: Introductionmentioning
confidence: 99%